An investigation on titanium doping in reduced graphene oxide by RF magnetron sputtering for dye-sensitized solar cells - Low F.W.; Lai C.W.; Asim N.; Akhtaruzzaman M.; Alghoul M.; Tiong S.K.; Amin N. (Elsevier Ltd, 2023)
Crystallinity; Doping (additives); Graphene; Light absorption; Magnetron sputtering; Morphology; Nanosheets; Oxide minerals; Reduced Graphene Oxide; Semiconductor doping; TiO2 nanoparticles; Titanium dioxide; Titanium metallography; X ray photoelectron spectroscopy; Phase formations; Reduced graphene oxides (RGO); rf-Magnetron sputtering; Sputtering process; Substrate distance; Surface chemical state; Thin film surfaces; Titanium doping; Dye-sensitized solar cells; chemical compound; detection method; equipment; fuel cell; inorganic compound; nanocomposite; titanium